(untitled) (Research, Society and Development, 2022)
In the past, man became largely responsible for the drastic reduction that occurred in the population of sea turtles, which was due to disorderly fishing and hunting for consumption. Considering the long life cycle and their late sexual maturation, chelonians have not yet been able to recover from this environmental disaster. The objective of this study is to gather information concerning the situation of sea turtles in the national territory, listing the main impacts suffered due to human action, and the gaps in current knowledge about these animals. Therefore, the narrative review was chosen because it allows for a broader discussion. The bibliographic search was carried out in the BVS, Scielo, Brazilian Portal of Scientific Information - CAPES and Google Scholar databases, complemented with a manual search in the reference lists of the selected works. Five turtles resort to the beaches of the Brazilian coast for spawning, feeding, breeding and resting: Dermochelys coriacea, Eretmochelys imbricata, Caretta caretta, Lepidochelys olivacea and Chelonia mydas. Despite the advancement and greater reach of environmental awareness, carried out by conservation organizations, the death of turtles due to human actions is still constant. Among the main activities are fishing, boat traffic, pollution and tourism. Therefore, it is essential to study and plan for the short and long term, the cause and its effects, not only for chelonians, but for the ecosystem as a whole.